Determination of Aquifer Depths in Muara Batu and Dewantara Sub-districts, North Aceh Regency, Using Vertical Electrical Sounding (VES) - Syafrizal Idris; Nanda Novita; Muliani Muliani; Muchlis Muchlis (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2024)
This study aims to determine the depth of aquifer layers in Muara Batu and Dewantara sub-districts, North Aceh Regency, Indonesia. The investigation was conducted at five location points (NA1, NA2, NA3, NA4, and NA5), each with a 600 m spread. Data collection at these points was carried out using the Vertical Electrical Sounding (VES) method with a Schlumberger configuration, utilizing the SuperSting R8/IP Resistivimeter. The data processing results produced resistivity cross-sections of the rock layers down to a depth of 150 m. Based on the cross-sections, the aquifer layers exhibit low resistivity values (<13.5 Ωm), consisting of sand, a mixture of sand and gravel, calcareous sandstone, and sandstone. The depths of potential aquifer layers at each measurement point are as follows: 35.9–150 m at NA1, 23.6–150 m at NA2, 54.5–150 m at NA3, 28.5–101 m at NA4, and 52.8–150 m at NA5. Points NA1, NA2, NA3, and NA4 show the presence of water-saturated layers starting at a shallow depth of 1.5 m. In contrast, NA5, located in a hilly area with complex geological conditions, has more resistive layers and limited groundwater potential compared to the other points.